Diversity‐Oriented Synthesis of Furo[3, 2‐c]coumarins and Benzofuranyl Chromenones through Chemoselective Acylation/Wittig Reaction. (5th January 2018) - Yang, Shu‐Mei; Wang, Chein‐Yi; Lin, Chun‐Kai; Karanam, Praneeth; Reddy, Ganapuram Madhusudhan; Tsai, Yi‐Ling; Lin, Wenwei
Abstract: A highly efficient and chemoselective one‐pot protocol for the diversity‐oriented synthesis of two types of coumarin‐based formal cross‐coupling adducts, furo[3, 2‐c]coumarins and 3‐benzofuranyl chromenones, is described. Key attributes of the methodology are an initial chemoselective acylation of functionalized phosphorus zwitterions and a subsequent chemoselective intramolecular Wittig reaction that preferentially resulted in one of the two coumarin derivatives in high yield, depending on relative reactivities and the addition sequence of the acylating agents.